Analysis of the impact of shear stress at the flange-web junction on the web behavior under concentrated and patch load. (December 2021) - Mijušković, Olga; Žugić, Ljiljana; Šćepanović, Biljana; Ćorić, Branislav
Abstract: This article focuses on realistic predictions of the buckling of web plates under concentrated and patch load conceptually isolated from I-beams or box-beams. Under certain simplifications (which usually approximate practical conditions), girder web can be treated, for two limiting cases, as simply supported or simply supported and clamped rectangular plate under in-plane non-uniform loads. Any problem, including very demanding patch loading case, can then be tackled accurately using Ritz's energy technique with double Fourier series for the deflection profile and exact stress distributions throughout the plate. The article firstly explains defined distribution of shear stresses on web-flange junction adopted, for the first time, in the analytical patch load model, and then proceeds to consider two different (but related) thematic problem types which concern various aspects of the introduction of such shear effect on stability problems of webs: firstly, how the shear stresses affect the buckling coefficients of plates and lead to an increase in load capacity due to more realistic web behavior and secondly, is there any influence of shear stresses on the existing values and shapes of interaction curves and surfaces. Analytical results in this article are compared with numerical finite element (FE) values.